A research update: Significance of cytokine storm and diaphragm in COVID-19 - Ashwani Mittal; Anita Dua; Sanjeev Gupta; Elisha Injeti (Elsevier, 2021)
Emerging research on severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) shows that it is spreading to multiple organs in addition to the respiratory system. Though the SARS-CoV2 enters the human body by binding to ACE2 receptors on pulmonary alveolar cells, recent studies indicate that it is spreading to the central nervous system, cardiac and skeletal muscles leading to various pathological conditions in these organs. In particular, the effects of SARS-CoV-2 on triggering the cytokine storm and its consequential effects on skeletal muscles has generated a lot of discussion. The effects of this virus on muscular function especially in susceptible elderly populations is still being explored. However, its effects on diaphragm, a respiratory muscle which plays an important role in determining lung capacity are not completely explored. Currently, as new evidence on using lung ultrasounds to confirm COVID-19 diagnosis is gaining traction, it is necessary to explore the role of diaphragm in treating COVID-19 patients. This article will review the effects of cytokine storm triggered by the SARS-CoV-2 and its resultant effects on skeletal muscle with a specific focus on the diaphragm in order to identify knowledge gaps in effectively treating COVID-19 patients, especially those who are on a mechanical ventilator.